Demand growth, entry and collusion sustainability - Carlo Capuano (Fondazione Eni Enrico Mattei (FEEM), 2002)
The purpose of this paper is to represent in which way a stable and no negligible growth in demand can affect the level of sustainability of collusion. For the European Commission this assumption is seen as a factor that disincentives collusion and pushes to a competitive behavior. This fact maybe is not so obvious and I have shown that what is important is the final effect on entry in the market. In fact, expected oligopolistic profits are as the Faith Morgana that attracts competitors and disappears when they have come in. Entry is profitable if it is finite, i.e. one or very few entrants, and if prices above marginal cost are still successfully sustainable.Our result is that demand growth path is not a sufficient condition to neglect the risk of collective dominance, and in order to support our analysis we consider first some trigger strategy equilibria where deviation punishment is implemented by Nash Reversion for ever. After that, we consider Abreu's simple penal code (1986) and we have derived a non stationary optimal penal code that in our structural changing framework implement collusion before and after entry as a subgames perfect equilibrium. The final conclusion is that demand growth, ceteris paribus, is negative correlated with the critical discount factor necessary to substaines collusion.
Keywords: L13; L4; L41; 330; penal code; merger control; demand growth; Kartell; Markteintritt; Fusionskontrolle; Gesamtwirtschaftliche Nachfrage; Theorie; EU-Staaten